Routledge international handbook of psychopathy and crime - DeLisi, Matt (Routledge international handbooks, 2019)
"For over two centuries, psychopathy has stood as perhaps the most formidable risk factor for antisocial behavior, crime, and violence. The Routledge International Handbook of Psychopathy and Crime presents the state-of-the-art on the full landscape of research on antisocial behavior that employs psychopathy as a central correlate. It is the largest and most comprehensive work of its kind, and includes contributions from renowned scholars from around the world. Organized into five distinctive sections, this book covers the etiology of psychopathy; the measurement of psychopathy; the association between psychopathy and diverse forms of homicidal and sexual offending, including serial murder, sexual homicide, rape and child molestation; criminal careers and psychopathy; the role of psychopathy in criminal justice system supervision, including institutional misconduct, noncompliance, and recidivism. This book is an essential resource for students and researchers in criminology, psychology and criminal justice, and will be of interested to all those interested in criminal behavior, sexual and violent crime, forensic psychology and forensic mental health"--